Patients' satisfaction, expectation, care, and maintenance of fixed prosthesis - Kashbur, Nada; Bugaighis, Iman (Libyan International Medical University Journal, 2019)
Aims: The aims of the present study were to evaluate the level of Libyan patients' expectations of and satisfaction with fixed prostheses (crowns, veneers, fixed partial denture, and dental implants). A further aim was to explore the level of patient's awareness and application of oral hygiene care pertaining to the fixed prosthesis. Materials and Methods: This was a cross-sectional survey. Self-reported questionnaires were administered to 320 patients wearing fixed prosthesis. The questions explored patient's subjective perception of and satisfaction with treatment outcome concerning esthetics, phonation, and masticatory function. In addition to questions related to their applied oral hygiene measures. Descriptive statistics and Spearman rank correlation coefficient tests were undertaken between the examined variables. P value was set at P < 0.05. Results: The majority (80.9%) of the patients were satisfied with their prosthesis; 78.4% were fulfilled with their chewing function; 85.3% were pleased with the esthetics; and 39.4% were satisfied by their speech. The fixed prosthesis met the expectations or partial expectations of 82.8% of the participants. Only 9.3% of the sample did not follow proper oral health care. There were moderate but significant correlation between the level of patients' expectations with and satisfaction from their prostheses (r = 0.387, P < 0.0001). Furthermore, the weak correlation between patient satisfaction and their application of oral hygiene measures was significant (r = 0.130, P = 0.020). Conclusions: Several factors (masticatory function, esthetic, and patient expectations) were correlated with the overall patients' satisfaction with their prosthesis. Dentist should continue to emphasize on the significance of maintaining good oral hygiene practice to improve patient satisfaction with their prostheses.
Keywords: Care and maintenance; fixed prosthesis; Libyan; oral hygiene; patients' expectation; satisfaction